The Harmony of Education and Upbringing as a Key Factor in Forming a Well-Rounded Individual - Muradova Zulfiya Kayumovna (Indonesian Journal Publisher, 2026)
This article evaluates the current state and effectiveness of the social protection system in Uzbekistan, focusing on its role in poverty reduction and welfare..The study analyzes government social assistance programs, the implementation of the